Systematic Literature Review: Pembelajaran Ekolitersi di Sekolah Dasar: Systematic Literature Review: Environmental Literacy Education in Elementary Schools - Satya Yulian Nur Azizah; Farida Farida; Yuli Yanti (Institut Agama Islam Daruttaqwa Gresik, 2026)
. The limitations of comparative studies on ecoliteracy learning in elementary schools in Indonesia and the United States highlight conceptual and empirical gaps in understanding differences in pedagogical approaches, curriculum integration, policy support, and their impacts on the development of students’ ecological knowledge, attitudes, and behaviors from an early age. This study aims to analyze and compare ecoliteracy learning practices in both countries, assuming that systematic curriculum integration, grounded in direct experience and supported by strong policies, will yield more comprehensive and sustainable ecological literacy outcomes than practices that remain partial or incidental. The subjects of this study are national and international scientific articles on ecoliteracy learning in elementary schools published in 2020–2025, which were analyzed using the Systematic Literature Review (SLR) method with the PRISMA approach through the stages of identification, selection, feasibility evaluation, and descriptive-qualitative data synthesis. The study results show that in Indonesia, ecoliteracy implementation is mostly carried out through project-based learning, integration of local wisdom, and school programs such as Adiwiyata. At the same time, in the United States, it is more structured through standards such as the Next Generation Science Standards, which emphasize experiential learning, STEM integration, and strengthening systemic thinking. The discussion of the findings confirms that the effectiveness of ecoliteracy is greatly influenced by teacher readiness, facility support, community involvement, and consistency of education policies. Therefore, strengthening professional training and continuous curriculum integration are strategic recommendations for improving the quality of environmental education in elementary schools.